How Small-scale Fishermen Survive During the Pandemic of Covid-19 - Suci Rahmawati Prima; Ake Wihadanto; Ni Made Ayu Krisna Cahyadi (Universitas Ahmad Dahlan, 2023)
This study aims to examine how the Kendari Bay’s coastal fishermen survive during the Covid-19 pandemic, especially from an economic perspective. However, the Covid-19 pandemic that occurred in the last three years has been able to shake the economy in several levels of society, including small-scale fishermen. The object of this research is 50 small-scale fishermen on the coast of Kendari Bay with data collection methods using surveys and interviews. Data analysis was carried out to reveal the characteristics of small-scale fishermen on the coast of Kendari Bay, to examine the impact of the COVID-19 pandemic on fishermen's income, and the constraints faced by fishermen from an economic perspective. The results show that small-scale fishermen averagely work as fishermen from a young age, as a form of inheritance from their parents and cannot complete basic compulsory education. Surprisingly, the Covid-19 pandemic does not have much impact on fishermen's income because the biggest impact comes from weather factors and the high cost of boat fuel. One of many issues that the fishermen need to deal is the difficulty on accessing capital and financial to start a business. This is happening due to limited information for these fishermen. The novelty of this research is in the study of the impact of the pandemic which is associated with access to public finance.